2006
DOI: 10.1093/ptj/86.7.944
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric Properties of the Performance-Oriented Mobility Assessment

Abstract: Background and Purpose. The Performance-Oriented Mobility Assessment (POMA) is a widely used instrument that provides an evaluation of balance and gait. It is used clinically to determine the mobility status of older adults or to evaluate changes over time. To support the use of the POMA for these purposes, the clinimetric properties (in particular, responsiveness) were determined. Subjects. Participants (78% female; mean age=84.9 years) were living in either self-care or nursing-care residences. Concurrent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
3
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(155 citation statements)
references
References 37 publications
3
133
3
16
Order By: Relevance
“…Bland‐Altman analyses indicated that systematic errors were not observed in the two sessions. Furthermore, a difference between the two session values that was smaller than the MDC could not be reliably interpreted as a “real change,” any different from chance fluctuations . Thus, the absolute test‐retest reliability of the current measurement method was confirmed.…”
Section: Discussionmentioning
confidence: 86%
“…Bland‐Altman analyses indicated that systematic errors were not observed in the two sessions. Furthermore, a difference between the two session values that was smaller than the MDC could not be reliably interpreted as a “real change,” any different from chance fluctuations . Thus, the absolute test‐retest reliability of the current measurement method was confirmed.…”
Section: Discussionmentioning
confidence: 86%
“…The MDC was calculated as SEM × 1.96 × √2 24 and represents the smallest change in BP level; this could be interpreted as indicating that the changes in values within the MDC were caused by measurement errors, while changes larger than the MDC were judged as "true changes" with a risk rate of 5%. 25 We calculated the repeatability coefficients for each of the three measurement times. The repeatability coefficients were also expressed as a percentage of nearly maximum variation, ie, the interval encompassing four times the SD of the averaged duplicated measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The TGS ranges from 0 (most deviations) to 12 points (normal). The TGS has good interrater reliability (rϭ.80 -.89), moderate to good test-retest reliability (rϭ.72-.77), 27 and good intrarater reliability (rϭ.95). 28 The TGS was originally developed to identify abnormal gait 17 and takes 5 minutes to score.…”
Section: Methodsmentioning
confidence: 99%